Analisis Strategi Perekrutan dan Pola Kompensasi dalam Praktik Skema Piramida Berkedok Bisnis Multi Level Marketing Perspektif Ekonomi Islam - Nafilah Hemalina Putri; Mohammad Luthfillah Habibi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The development of modern business has given rise to various marketing models, one of which is Multi-Level Marketing (MLM). However, in practice, many parties misuse this system into a pyramid scheme, a business model that prioritizes profits from recruiting new members rather than from actual product sales. This phenomenon causes harm to society and raises moral as well as religious concerns in Islamic law. This study aims to analyze the recruitment strategies and compensation patterns used in pyramid schemes disguised as MLM, examine them from the perspective of Islamic economics, and provide a comparison with Multi-Level Marketing systems that operate in accordance with Islamic principles. This research employs a descriptive qualitative method with a literature study approach by reviewing various sources such as books, scientific journals, and relevant academic documents. The results indicate that the recruitment system and compensation pattern in pyramid schemes contain elements of gharar, tadlis, dharar, and zhulm, all of which contradict Islamic economic principles. Therefore, the public is advised to be more cautious in choosing MLM businesses, as such models are permissible in Islam only if they focus on selling lawful (halal) products, are conducted honestly and transparently, and provide fair benefits for all parties involved.